Combatting Child Marriage - Tagorda, Yasmin Abdurahim (Journal of Contemporary Sociological Issues, 2024)
Numerous initiatives, including one in the Philippines, have been developed around the world to support the demand to end child marriage. Child marriage is widely practiced in indigenous and Muslim communities in the Philippines, but Republic Act No. 11596, known as the "Prohibition of Child Marriage Law," made it illegal in January 2022. Several actors, including youth groups in Muslim Mindanao, are seen as participants in this great success. This study aims to investigate the engagements and contributions of two Bangsamoro youth civil society organizations (CSOs) in this advocacy to recognize youth participation. Also, this study uses an institutional approach to seek and identify the enabling environment for youth participation in their quest to become active agents of positive change. Qualitative approaches are used to collect data from CSO youth members and other key informants. The findings imply that institutionalizing participation venues and the availability of initiatives funded by diverse donors promote robust youth engagement. Respondents also identified community involvement and school-based leadership development as motivators for joining and forming organizations. Networks among Bangsamoro youth groups encourage involvement and provide support in the pursuit of their advocacy. Intergenerational differences, on the other hand, limit youth engagement. Keywords: Bangsamoro Autonomous Region, CEFM, Youth-led engagement, Civil society organizations, Institutions